The return to gold dinar: historical and practical analysis - Mohamad, Ani Munirah; Md Nor, Mohd Zakhiri; Mahdzir, Nazli (2009)
This paper initially discusses the brief history of gold dinar as currency and its flow until it is replaced with the current fiat money system.The objective of this paper is to show that the recent idea in Malaysia to introduce gold dinar as monetary currency in Muslim countries is not a workable idea.Despite the destabilizing potential of the current monetary arrangements in the world, the return to gold dinar is neither desired nor practicable. The proposers of the idea are shown to be talking non-workable idea. This paper argues that the implementation of gold money in Muslim countries is in no way an Islamic compulsion, as there is neither any ruling that says Muslims are required to resort to gold money, nor there is any that says Muslims cannot resort to fiat money. And, even if gold money is enforced, the system is likely to end in a failure.Hence, it is suggested that the public policy must be guided by rationale, and not emotions.